Unveiling the experience of teachers in educational parlance: The post pandemic era of Covid-19 - Z. Agcaoili, Josiefel (Kasetsart Journal of Social Sciences, 2026)
The COVID-19 pandemic significantly disrupted global education, compelling educators to rapidly adapt to remote learning environments. This study examines the experiences of higher education teachers in the Cagayan Valley, Philippines, during this unprecedented shift. Utilizing a phenomenological research design, ten educators were interviewed to explore the personal and professional challenges they faced, including technological difficulties, mental health concerns, and student engagement issues. Findings reveal that while the abrupt transition posed substantial obstacles—such as adapting teaching methodologies and ensuring assessment integrity—educators also demonstrated resilience and innovation. Coping mechanisms ranged from the adoption of blended learning strategies to increased collaboration among peers. The study highlights the critical need for educational institutions to develop frameworks for crisis management, ensuring better preparedness for future disruptions. This research informs effective strategies that can enhance the educational landscape in times of crisis, ultimately promoting a more adaptable and resilient educational system.